2017
DOI: 10.21833/ijaas.2017.012.044
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian women entrepreneurial characteristics, strategic orientation and firm performance: The moderator role of government support programs

Abstract: This paper aims to identify critical factors associated with women entrepreneurship using the Malaysian small and medium enterprises (SMEs) as a base. The study also examines the government support program (GSP) as a mediator between the influencing factors and performance of women entrepreneurs. More publications on specific issues regarding women entrepreneurship are now available in the literature due to the increasing awareness on women entrepreneurs of different backgrounds. Despite the significance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Further, the moderating role of government support has been studied by (Bahari, Yunus & Jabar, 2017) in context of entrepreneurial orientation (EO) and SMEs success relationship and it confirmed the meaningful influence of government support. As the theoretical gap in previous researches related to entrepreneurs' competencies (EC) and SMEs financial success, this research intended to adapt the government support as a moderator.…”
Section: Moderating Effect Of Government Support On Financial Literacmentioning
confidence: 66%
“…Further, the moderating role of government support has been studied by (Bahari, Yunus & Jabar, 2017) in context of entrepreneurial orientation (EO) and SMEs success relationship and it confirmed the meaningful influence of government support. As the theoretical gap in previous researches related to entrepreneurs' competencies (EC) and SMEs financial success, this research intended to adapt the government support as a moderator.…”
Section: Moderating Effect Of Government Support On Financial Literacmentioning
confidence: 66%
“…, Lisboa et al (2016),Danso et al (2016),Bahari et al (2017),Ozaralli and Rivenburgh (2016),Mahmood et al (2017), Meroño-Cerdán et al (2018 andIsaga (2018). On the other hand, other personality traits such as need for achievement (Hypothesis 1) and propensity of risk taking (Hypothesis 3) were not shown to have a positive link with performance of SEPs by results (H1: b = -0.014, t = 0.179; H3: b = 0.060, t = 0.870).…”
mentioning
confidence: 85%
“…Besides, the government must provide non-financial support through seminars and training workshops for SMEs entrepreneurs' to mitigate the consequences of inadequate entrepreneur competencies (EC) and financial literacy. Bahari et al (2017) has studied the moderating role of government support on the relationship of entrepreneur orientation (EO) and SMEs business success in Malaysian context and has confirmed the moderating role of government support. Further, Shamsuddin et al (2017) confirmed that financial support, non-financial support and other business support from the government is positively related to SMEs business performance.…”
Section: Introductionmentioning
confidence: 93%